Heat conservation during cold exposure in birds (vasomotor and respiratory implications) - Johansen, Kjell; Bech, Claus (Polar Research, 2010)
The mechanisms by :vhich peripheral circulation and respiration serve in maintaining thermal homeostasis in birds living in cold climates are reviewed. Three types of arteriovenous heat exchanger (an elaborate rete, asimple rete, and a venue comirantes system) are found in the legs of birds. The anatomical differences between the different types of A-V associations are described, and the regulation of peripheral blood flow, in respect to maximal heat conservation and prevention of tissue damage, is discussed. A nasal temporal counter current heat exchanger, lowering the temperature of the expired air to values considerably below the body temperature, is the most important mechanism for minimizing the respiratory heat and water loss. In addition, a decreased ventilatory requirement, caused by a changed respiratory pattern and an increased parabronchial oxygen extraction, lowers the amount of air ventilated relative to the amount of oxygen uptake. Thus, the relative loss of heat and water is reduced.
Keywords: Antarktis; fugler; kuldeeksponering; kuldetoleranse; ornitologi; zoofysiologi; zoologi